Nickel acquisition affected by root density of mono- and mixed-cropping peanut and choy sum - Aiyen Tjoa; Leisa Reclina Christi; Nur Edy; Zainuddin Basri; Henry Barus (Foresty Faculty of Hasanuddin University, 2023)
Nickel (Ni) and associated minerals (Cr and Mn) are naturally occurring substances in ultramafic laterites soil. It may be found in our vegetables and grains when agriculture is grown in ultramafic laterites. This study aimed to assess the contamination of Ni in edible crops affected by soil volume in mono- and mixed cropping on limonitic laterite soil. The investigation was conducted on Peanut (Arachis hypogaea L.) and Choy Sum (Brassica rapa var. parachinensis) in three different pots sizes-representing soil volume to support root growth, which was filled with 0.5 kg (small), 1.0 kg (medium), and 1.5 kg (big) of limonitic laterite soil, respectively. The limonitic soil has a 7.884 mg kg-1 Ni concentration. The experiment shows that Ni concentration in peanut and Choy Sum shoots of mono-cropping in small, medium, and big pots achieve 20, 90, 120 mg kg-1 and 51, 67, and 95 mg kg-1, respectively. Meanwhile, in mixed cropping, Ni concentration in small, medium, and big pots of peanut and Choy Sum shoots are lower only by 33, 50, and 51 mg kg-1 and 15, 52, and 63 mg kg-1, respectively. Contamination of Ni in Peanut and Choy Sum shoots increases with the increasing soil volume, and mixed cropping is a potential strategy to reduce the acquisition of Ni.